Retrospective Analysis of Ultrasound-Guided Infraclavicular Block: Effect of Experience of Anesthesiologists on Volume of Local Anesthetic Administered - Tugce Yeniocak; Nur Canbolat (Pain Research and Management)
Performing a block under ultrasound guidance effectively requires skill; however, inexperienced anesthesiologists often use high-dose LA to ensure success. We aimed to share our experience with the ultrasound-guided infraclavicular brachial plexus block (USGICB) for upper extremity surgeries and to determine changes in failure rate and local anesthetic dose administered with gaining adequate experience. With approval from the local ethics committee, a retrospective review of records of 2953 patients who underwent USGICB between November 2011 and March 2015 was performed for evaluating the following data: age, sex, height, weight, operation type, American Society of Anesthesiologists physical status score, local anesthetic volume, complications, and success of USGICB. The patients were divided into 4 groups of 10 months each from November 2011 to March 2015: first 10-month period, 628 cases (group I); second 10-month period, 672 (group II); third 10-month period, 720 (group III); and the fourth 10-month period, 933 cases (group IV). Nine anesthesiologists with the same baseline experience in USG performed the blocks. During the initial period, when anesthesiologists had insufficient experience, local anesthetic (LA) dose, success rate, failed blocks, and complications were investigated. The LA volume administered in group I (33.7 ± 4.2 ml) was significantly higher than that in groups II, III, and IV (p<0.05). Although a reduction in LA volume administered with increasing anesthesiologist experience was not statistically significant, a volume reduction of over 30 ml was observed in groups II, III, and IV compared with group I. Furthermore, in group I, failure rate (3.2%) was higher than that in groups II, III, and IV (p<0.05). We concluded that sonographic guidance ensures a high success rate and that increased experience of anesthesiologists is associated with reduced complications and failure rate of blocks, in addition to prevention of LA overdose.